The effects of wrist motion and hand orientation on muscle forces: A physiologic wrist simulator study - Shah, D. S.; Middleton, C.; Gurdezi, S.; Horwitz, M. D.; Kedgley, A. E. (Journal of Biomechanics, 2017)
Although the orientations of the hand and forearm vary for different wrist rehabilitation protocols, their effect on muscle forces has not been quantified. Physiologic simulators enable a biomechanical evaluation of the joint by recreating functional motions in cadaveric specimens. Control strategies used to actuate joints in physiologic simulators usually employ position or force feedback alone to achieve optimum load distribution across the muscles. After successful tests on a phantom limb, unique combinations of position and force feedback - hybrid control and cascade control - were used to simulate multiple cyclic wrist motions of flexion-extension, radioulnar deviation, dart thrower`s motion, and circumduction using six muscles in ten cadaveric specimens. Low kinematic errors and coefficients of variation of muscle forces were observed for planar and complex wrist motions using both novel control strategies. The effect of gravity was most pronounced when the hand was in the horizontal orientation, resulting in higher extensor forces (p < 0.017) and higher out-of-plane kinematic errors (p < 0.007), as compared to the vertically upward or downward orientations. Muscle forces were also affected by the direction of rotation during circumduction. The peak force of flexor carpi radialis was higher in clockwise circumduction (p = 0.017), while that of flexor carpi ulnaris was higher in anticlockwise circumduction (p = 0.013). Thus, the physiologic wrist simulator accurately replicated cyclic planar and complex motions in cadaveric specimens. Moreover, the dependence of muscle forces on the hand orientation and the direction of circumduction could be vital in the specification of such parameters during wrist rehabilitation.